A review on child and maternal health status of Bangladesh - A. H. M. Mahmudur Rahman (Wolters Kluwer Medknow Publications, 2018)
Child and maternal nutritional and health status is a very much concerning issue of Bangladesh. To summarize the specific conditions of Bangladeshi child and maternal health and related issues. This is a descriptive review and overall analysis and description of the literature was done regarding child and maternal health of the general population living in Bangladesh. The evidence reflected that infant, child, and maternal mortality in Bangladesh have declined gradually at least over the past years. It is found that infant mortality 2 times, child mortality 6 times, and under five mortality rates 3 times declined comparatively than the last two decades but it is noted that maternal assassination circumstance has not declined. Knowledge on child and maternal health carries an important role in education. Health knowledge index significantly improve child and maternal health although differentially. It is obvious that poverty is one of the root causes that have led to a high child and maternal mortalities and morbidities faced by the people of Bangladesh. The requirement for socio economic relief for those living in rural Bangladesh remains one of the core issues. Recently, Bangladesh is successfully declining the total number of childhood and nutrition related mortalities despites various complexities, but maternal health status is not improving at the same pace. Nongovernment and government funded organizations and policymakers should come forward for running some effective programs to conquer the situation completely in Bangladesh.